The Implementation of Scouting Extracurricular in Building Students' Character - Rohanah, Rohanah; Rahmawati, Intan; Agustini, Ferina (Universitas Pendidikan Ganesha, 2020)
Constraints to the implementation of character development through scout extracurricular activities have caused many students in the alert and mobilizing groups to focus more on the game than the material and there are still students who do not obey the scouting activity regulations. The purpose of this research was to analyze the implementation of character planting in students through scout extracurricular activities. This research was using a descriptive qualitative research. The population in this research was all students of SDN Tlogosari Kulon 06 Semarang, totaling 91 students. The validity of the data was obtained through two triangulations, namely technical triangulation and source triangulation. Collecting data through observation, interviews, and notes in the field. Tringulation technique for testing data creation. The data analysis method used was qualitative analysis method. The results of the analysis showed that the activities carried out during extracurricular scouting have implemented the planting of the five attitudes that need to be achieved by students. The students' religious, integrity, and nationalist attitudes are good, even though the implementation of the overall attitude has been carried out evenly, students still need an emphasis on independence and mutual cooperation. Most students still object to being made into a team with friends from other classes, they do not yet have the independence to go and use complete attributes when scouting extracurricular activities without having to be ordered and warned repeatedly by class teachers and coaches.